Analisis Pemanfaatan E-commerce Dalam Pengembangan Bisnis Pelaku Usaha Mikro, Kecil, dan Menengah (UMKM) di Era Revolusi 4.0 (Studi Kasus Pada UMKM di Kabupaten Malang) - Navilah Laila Wardani; Jeni Susyanti (Publikasi Inspirasi Indonesia, 2024)
This research was conducted using a qualitative descriptive method, and the technique used was interviews. Through interviews, the researcher can ensure that the answers given are accurate information and can delve deeper into the required information. In this research, the focus is on discussing e-commerce as the object of study because, in the era of the industrial revolution 4.0, many business actors use e-commerce services as a medium to develop their businesses. The purpose of this research is to find out the reasons why MSMEs use e-commerce, the reasons for not using other e-commerce platforms besides the ones currently used, and what obstacles are faced when using e-commerce as a medium to market products.